Physics Research in the University of Kerala: an Informetric Study of Doctoral Theses - Sudhier, K. G. (Journal of Information and Knowledge, 2011)
Research in Physics carried out at the Dept. of Physics, University of Kerala, South India during 1999-2003 have been analysed using Informetrics techniques to find out the trends and major areas for further research. The study also analysed the various bibliographic forms of references included in the theses and identified core journals and books cited. It was observed that journals and books are the most preferred bibliographic form of citations used by the physicists, and they are 82.08% and 12.92% respectively. The study indicates that the average number of citations of male scholars is more than that of female scholars but the number of theses of female scholars are more than the male scholars. The results of the study is aimed at appraising the physicists to make them aware of the direction of the ongoing research in physics.